Dear girls : intimate tales, untold secrets & advice for living your best life - Wong, Ali (Random House, 2019)
"In her hit Netflix comedy special Baby Cobra, an eight-month pregnant Ali Wong resonated so heavily that she became a popular Halloween costume. Wong told the world her remarkably unfiltered thoughts on marriage, sex, Asian culture, working women, and why you never see new mom comics on stage but you sure see plenty of new dads. The sharp insights and humor are even more personal in this completely original collection. She shares the wisdom she's learned from a life in comedy and reveals stories from her life off stage, including the brutal singles life in New York (i.e. the inevitable confrontation with erectile dysfunction), reconnecting with her roots (and drinking snake blood) in Vietnam, tales of being a wild child growing up in San Francisco, and parenting war stories. Though addressed to her daughters, Ali Wong's letters are absurdly funny, surprisingly moving, and enlightening (and disgusting) for all"--